Pengaruh Kualitas Informasi Akuntansi, Akuntabilitas, dan Transparansi Pelaporan Keuangan Lembaga Pengelola Zakat terhadap Pembayaran Zakat Muzaki dengan Aksesibilitas sebagai Pemoderasi - Syifa, Syifa; Anggraini, Dahlia Tri (Jurnal Akuntansi dan Governance, 2024)
Objectives: Most zakat funds do not flow to the Zakat Management Institution (LPZ). Therefore, this study aims to empirically test and analyze the influence of external factors that can influence muzaki to pay zakat through LPZ such as the quality of accounting information, accountability, and transparency of financial reporting, and accessibility of LPZ.Design/method/approach: This study uses a quantitative method sourced from primary data through the distribution of questionnaires (google form). The convenience sampling technique is used in determining the sample, namely one hundred muzaki who pay zakat through LPZ. Data analysis tools with SmartPLS software version 4.Results/findings: The quality of accounting information has a significant positive effect and accountability, transparency, and accessibility have an insignificant positive effect on zakat payments, but accessibility does not moderate the effect of factors that influence the payment of zakat.Theoretical contribution: Develop the field of LPZ accounting science that the accounting aspect is very important to study because it influences the development of an LPZ.Practical contribution: The research provides recommendations to LPZ to improve the quality of information, accountability and transparency in its operations because it greatly influences muzaki paying zakat in addition to ease of access.Limitations: This research model cannot predict the response variable, namely zakat payments, because the response variable is less reliable and the sample is less accurate. Another limitation is that most of the research results are not significant due to the large number of invalid research statement constructs